Controlling foamability of polypropylene/γ-irradiated ethylene acrylic elastomer blends by extent of crosslinking and domain microstructure of elastomer. (June 2022) - Dutta, Anindya; Banerjee, Debjyoti; Ghosh, Anup K.
Foams of polypropylene/elastomer blends can often lead to softer foams which may not be desirable every time. Incorporating rigidity to the foams can often be made possible by preferentially crosslinking the elastomer phase prior to blending. Although foamability of polypropylene/elastomer blends has been understood in the scientific community, the influence of the extent of crosslinking in the elastomer phase is not yet understood well. The purpose of this investigation is to identify the influence of the extent of elastomer crosslinking and the blend morphological attributes (achieved by varying screw speed during melt mixing) on foamability of polypropylene/partially crosslinked elastomer blends. Crosslinking of ethylene-acrylic elastomer is carried out using gamma radiation with several doses (0, 12.5, 25, 50 kGy) before melt blending and, subsequently, 10 wt.% of the irradiated elastomers (prior optimized) are mixed with polypropylene in a micro-compounder at three different screw speeds. The microstructure development in blends is characterized by scanning electron microscopy. Frequency sweep rheological analysis is done for selected blends to identify the ease of foamability among the series of blends. Foaming of blends is done with supercritical carbon dioxide in batch mode at three different temperatures. The density reduction along with the microcellular morphology development of blends with foaming is analyzed with the screw speed, the extent of crosslinking, and foaming temperature; furthermore, the individual input parameters (the elastomer domain size, controlled by the screw speed and the extent of crosslinking, controlled by gamma radiation dose) are optimized based on the foam morphology. A uniform and good foamability were achieved at 155 and 160°C for blends with elastomers, irradiated at 12.5 and 25 kGy radiation doses. The lowest density foam (0.37 g/cc) was obtained for polypropylene with 12.5 kGy irradiated crosslinked elastomer mixed at 200 rpm at 160°C foaming temperature. The final elastomer domain dispositions within the foam morphologies are characterized and the plausible foaming mechanism is proposed.